PENGARUH MODEL PEMBELAJARAN JOYFUL LEARNING TERHADAP HASIL BELAJAR IPAS KELAS IV UPTD SD NEGERI 125549 PEMATANGSIANTAR - Simanjuntak, Melvin; Desi Sijabat; Malika Situmorang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of using the Joyful Learning model on science learning outcomes of fourth-grade students at UPTD SD Negeri 125549 Pematangsiantar. This study used a quantitative approach. The research design used was an experiment, with a pre-experimental design, and the sample size was 20 students. The instrument used in this study was a multiple-choice test. The results of the hypothesis testing obtained data on the average results of the experimental class in the pretest (48.5) and posttest (84.25). The hypothesis was tested using a t-test, where t-test > t-table (13.900 > 1.729) with a significance level of 0.05. Therefore, it can be concluded that the use of the Joyful Learning model has an effect on the science learning outcomes of fourth-grade students at the UPTD of SD Negeri 125549 Pematangsiantar.